The reliability and intensity dependence of maximum mouth pressure during bench press exercise in healthy athlete - DUSAN BLAZEK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪Respiratory muscle strength is an important indicator of human health and sport condition. The aim of this study was to assess the test/retest reliability of mouth pressure (MP) measured by a created pressure sensor mouthpiece in the sitting position and during bench pressing at various intensities. Material and methods: ‪23 healthy athletes were measured in 3 separate sessions for MP in the sitting position and during flat bench press at an intensity of one repetition maximum (1RM), 3 x 90% of 1RM, 8 x 80% of 1RM and 12 x 60% of 1RM. Results: ‪The measurement device showed acceptable reliability with ICC (Intraclass correlation) ranging from 0.75 to 0.95, where the highest reliability was reached in between repetitions, and slightly decreased when measurements were done in different sessions. The ANOVA showed differences between mouth pressure at different exercise loads (F4, 56 = 22.18, p< 0.001),with the highest MP measured in the sitting position, followed by 90% of 1RM, 80% of 1RM and 60% of 1 RM load. Conclusions: ‪This study shows acceptable reliability of MP measurement by a mouthpiece device with piezo-resistant sensor. The MP depends on the exercise intensity during the bench press and is higher in sitting than in the supine body position.